Chronic changes in the articular cartilage and meniscus following traumatic impact to the lapine knee. Issue 2 (21st January 2015) - Fischenich, Kristine M.; Button, Keith D.; Coatney, Garrett A.; Fajardo, Ryan S.; Leikert, Kevin M.; Haut, Roger C.; Haut Donahue, Tammy L.
Abstract The objective of this study was to induce anterior cruciate ligament (ACL) and meniscal damage, via a single tibiofemoral compressive impact, in order to document articular cartilage and meniscal changes post-impact. Tibiofemoral joints of Flemish Giant rabbits were subjected to a single blunt impact that ruptured the ACL and produced acute meniscal damage. Animals were allowed unrestricted cage activity for 12 weeks before euthanasia. India ink analysis of the articular cartilage revealed higher degrees of surface damage on the impacted tibias (p=0.018) and femurs (p<0.0001) compared to controls. Chronic meniscal damage was most prevalent in the medial central and medial posterior regions. Mechanical tests revealed an overall 19.4% increase in tibial plateau cartilage thickness (p=0.026), 34.8% increase in tibial plateau permeability (p=0.054), 40.8% increase in femoral condyle permeability (p=0.029), and 20.1% decrease in femoral condyle matrix modulus (p=0.012) in impacted joints compared to controls. Both instantaneous and equilibrium moduli of the lateral and medial menisci were decreased compared to control (p<0.02). Histological analyses revealed significantly increased presence of fissures in the medial femur (p=0.036). In both meniscus and cartilage there was a significant decrease in GAG coverage for the impacted limbs. Based on these results it is clear that an unattended combined meniscal and ACL injury results in significant changes to the soft tissues in this experimental joint 12 weeks post-injury. Such changes are consistent with a clinical description of mid to late stage PTOA of the knee.